V.P. Menon: the unsung architect of modern India - Basu, Narayani (Simon & Schuster, 2020)
Filling credibly a gap in the story of India's transition from Raj to republic, in this provocative, sharp, and urgently resurrects from the margins a man of forbidding character with a near impenetrable mind; an celebrated stalwart whose contributions have languished behind the reputations of those with greater charm. Deftly and often very directly, Basu locates V. P. Menon in the midst of fascinating dynamics featuring race, power, constitutionalism, and personal animosities, making a long overdue contribution to our knowledge of the men and minds that shaped Indian independence and its democratic destiny.